Assessment of Company Competitive Advantage Strategy Through Supply Chain - N.A Medvedeva; A.O Merenkov; E.V Medvedeva (International Journal of Supply Chain Management, 2020)
Abstract— The article discusses the methodological aspects of an enterprise competitiveness improvement based on the strategic development of supply chain management. In modern conditions, a high level of quality provision in enterprise activities is becoming an important factor forming a competitive advantage in the context of enterprise struggle increase both during the economic recovery and during the period of financial decline in various economic and political situations. The aim of the work is to justify the methodological aspects of the company competitive advantage strategy evaluation through the supply chain management. The study proposed an algorithm for a competitive advantage strategy selection using the example of a modern pulp and paper mill, developed the methodology for assessing the impact of strategic competitive abilities on company sustainable development, and identified strategic competitive advantages. Our model confirmed the relationship between supply chain management measures (strategic partnership with supplier, customer relationship management, informing level, informing quality and procrastination) and a competitive advantage’s component.